Additive manufacturing of martensitic stainless steel matrix composites with simultaneously enhanced strength-ductility and corrosion resistance. (1st April 2022) - Chen, Wei; Xiao, Bo; Xu, Lianyong; Han, Yongdian; Zhao, Lei; Jing, Hongyang
Abstract: Many traditional methods for strengthening martensitic stainless steel (SS) typically come at the sacrifice of ductility. Herein, we report a configuration design of ceramic particles for reinforcing additively manufactured 15-5 PH martensitic SS with an optimized combination of high-strength and impressively larger ductility via the micron-sized TiC addition. High strength is ascribed to grain refinement, Orowan bowing strengthening, and abundant nucleation of nanoscale (Nb, Ti)C precipitates, while high elongation correlates to the reduced oxide inclusion content, martensite/austenite duplex microstructure, and progressive transformation-induced plasticity effect. In addition, severe localized corrosion is completely inhibited. This work shows the great potential of additive manufacturing technology to fabricate Fe-based composites with unique microstructures, low residual stress levels, excellent corrosion resistance, and an exceptional combination of strength and ductility for practical applications.